The air and noise situation in the alpine transit valleys of Fréjus, Mont-Blanc, Gotthard and Brenner - Jürg Thudium (Revue de Géographie Alpine)
The environmental consequences of road transport with regard to air and noise in the transit valleys of Fréjus, Mont-Blanc, Gotthard, and Brenner have been analysed and compared with each other for the year 2004. In respect of the share of transport passing through the Alps in transport as a whole, there are in part considerable differences between the valleys under investigation as well as within the individual valleys. The air pollution produced per emission unit of road transport is two to three times higher than in the open country, mainly because of the topography and the climate. At numerous monitoring points, the thresholds for the air pollution were exceeded. With regard to noise, the valleys are affected equally bad: The “amphitheatre effect” carries the noise to the higher reaches that would not be exposed to so much acoustic irradiation if the source of noise was situated at the same distance in the open country; furthermore, protection from the noise reflected by the slope is difficult. In aggregate, all transit valleys under investigation can be considered as sensitive regions.